Population status and feeding behavior of black kite (Milvus migrans) in Dhaka city, Bangladesh (Jahangirnagar University Journal of Biological Sciences, 2021)
The status and feeding behavior of black kite (Milvus migrans) in Dhaka city were studied from July 2015 to June 2017. Road transects and morning roost-count method were used for population estimation and distribution, whereas focal sampling method was used to study the feeding and foraging behavior. Based on roosting and foraging areas, five transects were selected for population estimation. Moreover, six different feeding areas were selected for identifying various types of consumed food and assessing the feeding behavior of black kite. The black kite population was estimated at (1296±5.87) in Dhaka city. The population density was estimated at 21.8/km2. Among selected five different transects, the recorded population ranged from 108.12±6.70, 8.34%) at S-3 (Mirpur to Ramna Park) to 805±11.88, 62.11% of individuals at S-5 (Gulistan to Demra). The present study revealed that black kites were distributed throughout the study area and the distribution was influenced by availability of food, water and roosting place. Based on the annual records, the highest population (1510±6.92) was found in 2016. Majority of black kites fed on offal and insects in study area. In garbage dumps, the highest rate of feeding was recorded in afternoon followed by in morning and lowest in the noon. Whereas in non-garbage feeding areas, the highest rate was recorded in the morning followed by in the afternoon and lowest in the noon. Among four different foraging strategies, food collection by kites standing on the ground and intraspecific cleptoparasitism was never observed during study period while interspecific cleptoparasitism (against crows) was the highest number (193.67±2.77, 68.43%).Jahangirnagar University J. Biol. Sci. 9(1 & 2): 35-48, 2020 (June & December)